Activities Based Contextual and Constructivist Learning: A Model for Enhancing Students’ English Learning Outcomes - Sofiana, Nina; Mubarok, Husni; Kristina, Diah; Rochsantiningsih, Dewi (KnE Social Sciences, 2022)
Changes from the current curriculum in Indonesia to the Merdeka Belajar (independent learning) curriculum require teachers to make learning more meaningful and fun for students by connecting concepts to the real world. This study aimed to develop a learning model with constructivism and contextual teaching and learning (CTL) approach to improve students’ English skills. The specific objectives of this study are to map the English learning model that has been implemented by teachers, identify the needs of students and teachers for the English learning model, develop a learning model with CTL and constructivism approaches, and test the feasibility of the model. The data were collected through observation, interviews, documentation, questionnaires, and tests in 12 public and private SMP/MTs spread across the Jepara, Demak, and Kudus districts. The collected data were analyzed qualitatively and quantitatively. Based on qualitatively collected data, students and teachers need a learning model that can provide students with learning experiences that are more meaningful. The developed model was proven effective by the value of the effectiveness test where the t-test results show greater than the t-table. Therefore, it implies that the learning models based on CTL and constructivism can be an alternative to the current learning models that can be applied to learning English at school. Keywords: Meaningful activities; contextual learning; constructivism learning.